Efficacy of a training program for parents to improve oral communication and the behavior of their children: a preliminary study - Puertas González, Jose Antonio; Ruiz Castilla, María; Fresneda López, María Dolores; Godoy García, Juan Francisco (Revista de Investigación en Logopedia, 2019)
The objective of the present study was to design, apply and analyze the effectiveness of a training program for parents, aimed at improving difficulties in speech and / or language and aimed at the treatment and prevention of behavior problems, in children from 3 years to 5 years and 11 months old. A quasi-experimental study was carried out with an experimental group (10 families) and a control group (7 families). The families were selected from the Elena Martín Vivaldi Infant and Primary School (Granada) and the program was composed of 12 sessions. The two groups were evaluated before and after the program. The experimental group improved their behavior in comparison with the control group, in addition, both groups increased their scores in various language assessment instruments. However, only the group that received the intervention presented improvement in the content dimension of the language, through the Prueba de Lenguaje Oral de Navarra Revisada. This study provides preliminary evidence on the effectiveness of the program in improving behavior and language in preschool children, however, more studies are needed.
Keywords: behavior problems; speech difficulties; language difficulties; training for parents